Keberhasilan Difusi Inovasi Gagasan Social Enterprise dalam Pemberdayaan Masyarakat Islam: Studi Komunitas Kampung Marketer Purbalingga - Wahanani Mawasti (JURNAL AT-TURAS, 2021)
Diffusion of innovation is an important part in the process of da'wah and empowerment of Islamic society. This article describes the strategies and success factors for the diffusion of innovation in the Islamic community empowerment programs implemented by Kampung Marketer in village communities in Purbalingga district. The method used is qualitative with in-depth interview techniques and is supported by documentation and online research. The results showed that the success of Kampung Markater in diffusing innovation was due to the characteristics of innovation that had relative advantages, compatibility, easy complexity, triability and observability. In addition, the success of the innovation diffusion process in rural communities is also supported by the components of the social system, such as: 1) agents of change characteristics, 2) homophilia between agents of change characteristics and adopters, 3) characteristics of adopters, 4) social norms of the community and 5) the communication channels used. The community figure component also has an influence on the spread of innovation but is not very dominant